Analisis Bahasa dalam Buku Pengayaan Digital Literasi Bermuatan Eco Green untuk Siswa Sekolah Menengah Pertama - Sumirah Sumirah; Ida Zulaeha; Hari Bakti Mardikantoro; Haryadi Haryadi (SAWERIGADING, 2025)
This study aims to analyze the linguistic characteristics in digital literacy enrichment books with eco green content for junior high school students. The main focus of the research is how language is used contextually, transformatively, and interactively to build environmental awareness and improve students' literacy skills. This research used a qualitative approach with content analysis method. Data collection techniques included document analysis of digital books, observation of students' interaction with interactive features, and structured interviews with teachers and linguists. The data were analysed through three stages: text identification based on environmental themes, categorization into three linguistic approaches, and evaluation of language effectiveness through source triangulation. The results showed that the selection of specific diction, imperative sentence structure, and integration of digital features such as video tutorials and interactive infographics were able to connect environmental concepts with students' real actions. Language in the book does not only function as a conveyor of information, but also as an instrument of identity formation, active participation, and transformation of learning into meaningful social practices. This research confirms the important role of language in creating holistic and sustainability-oriented digital literacy media. AbstrakPenelitian ini bertujuan untuk menganalisis karakteristik kebahasaan dalam buku pengayaan digital literasi yang bermuatan eco green untuk siswa Sekolah Menengah Pertama. Fokus utama penelitian adalah bagaimana bahasa digunakan secara kontekstual, transformasional, dan interaktif untuk membangun kesadaran lingkungan serta meningkatkan keterampilan literasi siswa. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis konten. Teknik pengumpulan data meliputi analisis dokumen terhadap buku digital, observasi interaksi siswa dengan fitur interaktif, serta wawancara terstruktur dengan guru dan ahli linguistik. Data dianalisis melalui tiga tahap: identifikasi teks berdasarkan tema lingkungan, kategorisasi ke dalam tiga pendekatan kebahasaan, dan evaluasi efektivitas bahasa melalui triangulasi sumber. Hasil penelitian menunjukkan bahwa pemilihan diksi spesifik, struktur kalimat imperatif, dan integrasi fitur digital seperti video tutorial dan infografis interaktif mampu menghubungkan konsep lingkungan dengan tindakan nyata siswa. Bahasa dalam buku tidak hanya berfungsi sebagai penyampai informasi, tetapi juga sebagai instrumen pembentukan identitas, partisipasi aktif, dan transformasi pembelajaran menjadi praktik sosial yang bermakna. Penelitian ini menegaskan pentingnya peran bahasa dalam menciptakan media literasi digital yang holistik dan berorientasi pada keberlanjutan